Awareness level of contractors in Perak towards the sustainable practice of construction waste on site / Nur Farhana Mohd Nadzir and Zaiwannizar Zainal Abidin - Mohd Nadzir, Nur Farhana; Zainal Abidin, Zaiwannizar (2019)
Nowadays, construction waste management in construction industry has become very demanding in Malaysia. As the construction waste produced by the construction activities are increasing on landfill, this problem may lead to shorter the life span of landfill. Waste reduction through Reduce, Reuse and Recycle (3R) practices have been encouraged in construction industry towards sustainable waste management since couple of decades ago. However, waste reduction through 3R are still at its infancy in construction industry. The aim of this study is to recommend ways to improve contractors’ awareness towards sustainable practice on site. The findings reported are based on feedbacks from construction contractors in Perak. Based on questionnaire surveys, recommendations identified are form specific law, organize awareness campaign, enforce the legislations, organize training sessions and provide guidelines. Therefore, these recommendations should be held by local authorities in order to improve the level of awareness of contractors towards sustainable practice on site.